The Influence Of Buzz Marketing And Brand Image To Purchasing Decision On Consumer Of Azarine In Bandar Lampung - Cika Nandita Roesly; Satria Bangsawan; Nuzul Inas Nabila (Yayasan pendidikan dzurriyatul Quran, 2026)
This study aims to analyze the influence of buzz marketing and brand image on purchasing decisions of Azarine consumers in Bandar Lampung. The research employs a quantitative approach with data collected through questionnaires distributed to Azarine consumers. The data were analyzed using statistical methods to examine the relationships and effects among variables. The results show that buzz marketing has a significant influence on purchasing decisions. Consumers are highly exposed to product information through social media, influencer content, and online promotional activities, which increase awareness, stimulate discussions, and encourage purchasing decisions. Furthermore, brand image also has a significant effect on purchasing decisions. Azarine is perceived as a well-known skincare brand with a positive image, which enhances consumer confidence and reduces uncertainty regarding product quality and safety. Positive brand associations, such as recognition, uniqueness, and favorable public perception, play an important role in building consumer trust and shaping purchase preferences. Overall, both buzz marketing and brand image contribute to purchasing decisions. Buzz marketing functions to attract attention and stimulate interest, while brand image strengthens consumer confidence and reinforces the final decision to purchase. Therefore, the combination of effective buzz marketing strategies and a strong brand image is essential for Azarine to maintain and improve its competitive position in the cosmetic market in Bandar Lampung.